Thriving in Digital Workplaces: How Digital Competency and Psychological Capital Shape Employee Well-Being under Technostressency and Psychological Capital Shape Employee Well-Being under Technostress - Yusuf Riyanto; Wiwiek Rabiatul Adawiyah; Ratno Purnomo; Najmudin; Sudarto (Global Research Collaboration, 2026)
This study examines the relationships among Digital Competency, Psychological Capital, Technostress, and Employee Well-Being by investigating the mediating role of Psychological Capital and the moderating role of Technostress. A quantitative explanatory design was employed using survey data collected from 100 SME employees. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Digital Competency positively affected Employee Well-Being and Psychological Capital. Psychological Capital significantly mediated the relationship between Digital Competency and Employee Well-Being. Technostress negatively affected Employee Well-Being but did not significantly moderate the relationship between Digital Competency and Employee Well-Being. This study contributes to Human Capital Theory and Conservation of Resources Theory by integrating Digital Competency, Psychological Capital, Technostress, and Employee Well-Being into a single moderated mediation framework.